impact of Chaim Soutine (1893-1943) : de Kooning, Pollock, Dubuffet, Bacon. - Dunow, Esti; Gmurzynska, Krystyna; Rastorfer, Matthias; Tuchman, Maurice; Galerie Gmurzynska, Köln (Ostfildern-Ruit : Hatje Cantz Verlag, 2002)
This exhibition and catalogue aim to reveal not only the seminal power and reverberant originality of Chaim Soutine's painting, but also the meaningful influence his work exerted on major post-War painters. It will be demonstrated how Soutine added depth and additional layers of expressiveness to the art of leading modern American, French, and British artists, whose artistic presence will enhance the truly historical scope of the exhibition.
Chronology and biography Chaim Soutine p. 142-145
Engels
The impact of Chaim Soutine : (1893-1943): de Kooning, Pollock, Dubuffet, Bacon, Galerie Gmurzynska Köln, November 2 - December 15, 2001
boek
Keywords: Soutine, Chaim; de Kooning, Willem; Pollock, Jackson; Dubuffet, Jean; Bacon, Francis